The Effect of Provision and CSR on Banking Financial Performance Moderated by Non-Performing Loans - Pramesti Baskoro Dewi; Margaretha, Farah; Kristian Chandra (Business and Entrepreneurial Review, 2025)
This study aims to analyze the effect of loan loss provision (LLP) and corporate social responsibility (CSR) on financial performance (FP), moderated by non-performing loans (NPL). The data used in this study are secondary data sourced from the annual reports of companies in the banking sector listed on the Indonesia Stock Exchange (IDX) during the period 2019–2023. The research sample was selected using the purposive sampling method, resulting in 35 companies that met the criteria for sampling. Multiple regression analysis using the E-Views program was used to test the hypothesis. The results showed that loan loss provision and corporate social responsibility as independent variables have a positive and significant influence on financial performance as the dependent variable. Furthermore, the non-performing loan variable, as a moderating variable, can weaken the relationship between loan loss provisions and corporate social responsibility on financial performance by exerting a negative influence. The results of this study provide insights and implications for both management and investors that a low level of non-performing loans can improve the bank's financial performance in line with increasing and maintaining the provision for impairment losses for bad loans, which in turn can also improve financial performance. Furthermore, the bank's consistency in committing to continue carrying out activities or social actions towards stakeholders is considered to have a positive impact on financial performance because a positive reputation can actually increase the company's value. With the increase in company value, it will certainly be attractive for investors to invest in the company.